2017
DOI: 10.1007/s11524-016-0109-y
|View full text |Cite
|
Sign up to set email alerts
|

How Feasible is Multiple Time Point Web-Based Data Collection with Individuals Experiencing Street Homelessness?

Abstract: Three barriers investigators often encounter when conducting longitudinal work with homeless or other marginalized populations are difficulty tracking participants, high rates of no-shows for follow-up interviews, and high rates of loss to follow-up. Recent research has shown that homeless populations have substantial access to information technologies, including mobile devices and computers. These technologies have the potential both to make longitudinal data collection with homeless populations easier and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Previous studies have identified numerous challenges to random sampling in survey research with homeless populations, including difficulties with enumeration, the transient nature of the population, and the very fact that homelessness is a fluid problem, with individuals often moving in and out of homelessness in a relatively short time span (Eyrich-Garg & Moss, 2017; Fitzgerald et al., 2001). Following standard practice in homelessness research (e.g., Eyrich-Garg, 2011; Guadgano et al., 2013; Rice & Barman-Adhikari, 2014), this study is based on a convenience sample of individuals recruited through the Los Angeles Public Library.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have identified numerous challenges to random sampling in survey research with homeless populations, including difficulties with enumeration, the transient nature of the population, and the very fact that homelessness is a fluid problem, with individuals often moving in and out of homelessness in a relatively short time span (Eyrich-Garg & Moss, 2017; Fitzgerald et al., 2001). Following standard practice in homelessness research (e.g., Eyrich-Garg, 2011; Guadgano et al., 2013; Rice & Barman-Adhikari, 2014), this study is based on a convenience sample of individuals recruited through the Los Angeles Public Library.…”
Section: Methodsmentioning
confidence: 99%
“…RLE may also improve upon the data collection instruments through which other implementation constructs are measured, such as reach ( Proctor et al, 2011 ). For example, if a harm-reduction intervention is designed for implementation with people who are unhoused (a notoriously difficult population to track; Eyrich-Garg & Moss, 2017 ), RLE may provide insight into how best to measure the overall reach of the intervention and/or follow enrolled subjects over time. Further, RLE can help identify practical outcome measures (positive or negative) beyond the typical abstinence measures in common practice ( Paquette et al, 2022 ).…”
Section: Improving the Adoption And Implementation Of Evidence-based ...mentioning
confidence: 99%